The Function of Communication in Human Life - Sari, Nopa Muspita; Kholia, Suci Lailatul (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
This discussion aims to find out what functions of communication are often carried out or seen in human life. In this discussion, we will explain the various functions of communication through social functions like what and how, then there are expressive and ritual functions like what and how, and then the function of communication as an instrumental function. The purpose of understanding and knowing the functions of communication is so that we can differentiate between one communication and another, and this discussion aims that we did not misuse the communication that we have used, so that good communication can be formed and by the rules that apply in all aspect of life. The method used in this discussion is the description method, where this method provides an explanation based on phenomena that have occurred and are often encountered in human life.